2018
DOI: 10.1002/jcp.27066
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Inhibitory role of large intergenic noncoding RNA‐ROR on tamoxifen resistance in the endocrine therapy of breast cancer by regulating the PI3K/Akt/mTOR signaling pathway

Abstract: Breast cancer (BC) is the second-leading cause of central nervous system metastases among severe malignancies. This study aimed at investigating the underlying mechanism by which large intergenic noncoding RNA-regulator of reprogramming (lincRNA-ROR) affects the tamoxifen (TAM) resistance of BC cells by regulating the PI3K/Akt/mTOR signaling pathway. Immortalized human mammary epithelial cell line (MCF10A) and BC cell lines (MCF-7, MDA-MB-231, T47D, BCAP-37, and ZK-75-1) were cultured, and BC tissues and adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…RoR is ∼2.6 kbp and is located on 18q21.31. RoR is an oncogenic lincRNA that is highly expressed in self-renewing human embryonic stem cells and various cancer cells such as hepatocellular carcinoma [93], endometrial cancer [94], pancreatic cancer [95] and BC [[96], [97], [98]]. In several contexts, there is a positive correlation between the expression level of RoR and the undifferentiation degree of the carcinoma tissues [99].…”
Section: Introductionmentioning
confidence: 99%
“…RoR is ∼2.6 kbp and is located on 18q21.31. RoR is an oncogenic lincRNA that is highly expressed in self-renewing human embryonic stem cells and various cancer cells such as hepatocellular carcinoma [93], endometrial cancer [94], pancreatic cancer [95] and BC [[96], [97], [98]]. In several contexts, there is a positive correlation between the expression level of RoR and the undifferentiation degree of the carcinoma tissues [99].…”
Section: Introductionmentioning
confidence: 99%
“…We found that TDH had a significant concentration-dependent inhibitory Evidence-Based Complementary and Alternative Medicine effect on the proliferation of human colon cancer LoVo cells in vitro; moreover, it can also induce apoptosis and inhibit the migration of LoVo cells; these results indicated that TDH could inhibit colon cancer cell viability and metastasis. e abnormal activation of the PI3K/AKT/mTOR signaling pathway has been observed in a variety of human tumors, including esophageal, ovarian, breast, and colorectal cancer and promoted the development of tumor by promoting cell proliferation, inhibiting apoptosis, or activating angiogenesis [16][17][18][19]. e aberrant activation of the Wnt/β-catenin signaling pathway has been also demonstrated in colorectal cancer and regulates gene expression and cell invasion, migration, proliferation, and differentiation in the initiation and progression of CRC [20].…”
Section: Discussionmentioning
confidence: 99%
“…In TNBC tissues [202,203] and cell lines [201,202,203], the level of lincRNA-ROR is increased. Overexpression of lincRNA-ROR in TNBC cell line MDA-MB-231 promotes cell invasion and metastasis, while inhibition of lincRNA-ROR expression exerts the opposite effects [202,204].…”
Section: Lncrnas In Breast Cancer (Bc)mentioning
confidence: 99%